FAKTOR-FAKTOR YANG BERHUBUNGAN ORANGTUA MENIKAHKAN ANAK PADA USIA DINI DI WILAYAH KECAMATAN WONOSARI - Yati, Dwi; Citra, Rabiah Sundari (Universitas Muhammadiyah Magelang, 2020)
The percentage of female aged between 15-19 years old who have early marriages of the female 11.7 %, and the percentage of male is 1.6 %. This marriage is caused by some factors namely education, economy, and knowledge. This early age marriage will impact on women?s reproductive health that can endanger childbirth and in infants can occur LBW, besides that woman can also be exposed to other diseases such as cervical cancer. This research aims to find out factors that affect parents? decision to wed their children in early age in Wonosari sub-district. This is a quantitative research using analytic correlation design with cross sectional approach. The sample was selected through purposive sampling consisted of 65 respondents of parents who wed their children aged under 20 years old and parents who wed their children aged above 20 years old. The data were gathered on June 17th- 21th 2019 using questionnaires. The result of chi-square test and logistic regression shows variables that have correlation with the parents? factors to wed their children in early age are education (p=0.004), economy (p=0.014) and parents? knowledge (p=0.031) and logistic regression (p=0.0288). The result of logistic regression shows the most dominant factor that affects parents? decision to wed their children in early age is the third factor that is the economy factor. There is a correlation between education, economy and knowledge.